Comprehensive pan-cancer analysis of PTGES3 and its prognostic role in hepatocellular carcinoma - Wang, Han; Sun, Peng; Yao, Ruoyu; Zhang, Wenrui; Zhou, Xiaoshuang; Yao, Jia; He, Kun (Frontiers in Oncology, 2023)
The PTGES3, also known as p23, is a molecule chaperon of Hsp90 that involves in the pathogenesis of malignant tumor. Increasing studies have shown PTGES3 plays an unnegligible role in tumor development. However, analysis of PTGES3 in pan-cancer has not been performed yet. Therefore, we aimed to explore the role of PTGES3 in 33 types of tumors and depicted the potential immune-related pathways among them. Using multiple databases including TCGA, LinkedOmics, GDSC, and TIMER, we made a comprehensive analysis to explore whether there was an interaction between PTGES3 and prognosis, DNA methylation, copy number variation (CNV), tumor mutational burden (TMB), microsatellite instability (MSI), and tumor immune microenvironment (TME). And the results revealed that PTGES3 expression level was upregulated in most cancers. PTGES3 was also associated with prognosis positively or negatively in variety of cancers, which was mainly related to DNA methylation, CNV, MSI, TMB, and mismatch repair related genes. High PTGES3 expression was related to the infiltration of Th2 subsets of CD4+ T cells and immune checkpoint related genes in most cancer, especially in hepatocellular carcinoma (HCC). Enrichment analysis demonstrated that PTGES3 was involved in cellular processes including DNA replication and spliceosome. The relationship between PTGES3 expression and HCC progression was verified in protein level through the immune histochemical analysis. Our research demonstrated the prognosis predictive value of PTGES3 in a wide range of cancers, which was also connected to the process of tumor immune infiltration. As a result, it suggests that PTGES3 was a valuable prognostic biomarker in HCC treatment.